Novel SZT2 mutations in three patients with developmental and epileptic encephalopathies - Sun, Xiaomin (Mol Genet Genomic Med, 2019)
BACKGROUND: The seizure threshold 2 (SZT2) gene encodes a large, highly conserved protein that lowers seizure threshold and may also enhance epileptogenesis. In this study, three patients diagnosed with SZT2‐related developmental and epileptic encephalopathies (DEEs) were reviewed aiming to expand knowledge of the genotype and phenotype of SZT2 mutations. METHODS: Targeted next‐generation sequencing was performed to identify pathogenic mutations in 205 cases with DEEs of unknown etiology. Detailed clinical and genetic data were collected from SZT2‐associated patients. RESULTS: Four novel mutations were found (c.1626 + 1G>A, c.5772dupA, c.4209C > A, c.7307_7308insG) in three patients. All the variants were inherited from their parents. Two patients were siblings and harbored the same mutations and presented developmental delay prior to the onset of seizures. All the individuals were diagnosed as DEEs, drug refractory epilepsy, and experienced status epilepticus (SE); one patient died of SE. One subject showed subependymal nodules as similar as those of tuberous sclerosis complex (TSC) in cranial magnetic resonance imaging (MRI). CONCLUSION: Our results expand the genotype and phenotypes of SZT2‐related DEEs, suggesting that SZT2 mutations play a role in developmental delay and epileptic encephalopathy, with high susceptibility to SE and relatively specific MRI findings.